Design, Analysis and Fabrication of A Mini-Sailplane for Didactic Purposes In the Area of Development of UAV’s/MAV’s - Danish, Mohd; Arfin, Zainul; Jamil, Azhar; Mohd. Yahya, Syed (CFD Letters, 2021)
This paper is dedicated towards the design and fabrication of a mini sailplane with the aim of maximizing the glide ratio CL/CD. And at the same time minimizing the weight of the plane. For this NACA 7037 airfoil was selected for subsonic domain corresponding to low Reynolds number varying within the range of 105 to 3×105 as per the recommendations from literature [1]. A cambered NACA 7037 was fabricated from the wooden material and was experimentally investigated with different range of velocities and angle of attack for coefficient of lift and drag using wind tunnel setup. The same was numerically investigated using the commercial Finite Element Analysis FEA code of ANSYS FLUENT®. The results compared very well with the experimental one, thereby validating the computational fluid dynamics CFD model. This CFD model was applied to mini sailplane which has cambered profile made up of Balsa wood. Initially, flow around the wing was investigated in order to determine the optimal design for wing by comparing lift, lift-to-drag ratio, stalling characteristics and pitching moment. Finally, the entire sailplane was analysed to get the overall aerodynamic characteristic of the assembly. Main-plane and tail-plane distance was optimized along with the areas of the control surfaces for maximizing L/D ratio and certain designing rules were established. Drag, lift coefficient and pitching moment have been discussed and the appropriate conclusion was drawn. The experiment and calculation showed a significant improvement in the sailplane performance after using an optimized wing configuration.